Analysis of Factors Affect to Organizational Performance in Using Accounting Information Systems Through Users Satisfaction and Integration Information Systems - Anton Arisman; Lukluk Fuadah (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2017)
The aim of this research is to investigate the factors affecting organizational performance in using accounting information system through users satisfaction and integration information systems. The research respondents were 447 companies that listed in Indonesian Stock Exchange. The data are gathered through consensus method and in total there are 176 responses with complete data. Structural Equation Model (SEM) is used in analyzing the data and system theory is utilized in this research. The result shows that knowledge management systems and management control system have significant influence on users satisfaction and integration information systems.  Integration information system and users satisfaction has positive significant on organizational performance.